Genetic determinants of metabolism: clinical applications in psychiatry - Stingl (formerly Kirchheiner), Julia (Henry Stewart Talks, 2007)
Factors that determine psychiatric importance of genetic variants, Consequences which arise from genotyping, Drugs are metabolized via the polymorphic cytochrome P450 enzyme CYP2D6, Differences in pharmacokinetic parameters for tricyclics, some SSRIs, other antidepressants, typical and some atypical antipsychotic drugs, Effects on therapeutic efficacy and adverse events, Indication for genotyping in psychotropic drug treatment, Future research to close the gap between pharmacogenetic research and clinical practice
Archived at 2021/02/25